Modeling the Influence of Bridging Course on the Accounting Performance of the University Students using Educational Data Mining - Trecene, Jasten Jeneth; Jr, Eduardo Edu Cornillez; Barbosa, Reynalyn; Santos, Jessie Richie delos; Gultian, Erap (FKIP Universitas Lampung, 2021)
Modelling the Influence of Bridging Course on the Accounting Performance of the University Students Using Educational Data Mining. Objectives: This study intends to determine the level of performance of the students in their Bridging Course (BC) and Accounting Education (AE) courses, and to model their significant influence. Methods: Descriptive and Predictive Correlation research design was used. The Educational Data Mining technique was utilized to extract data from the database of the university. Out of 331 datasets extracted, only 281 were included in the analysis, where datasets with no grades, and with dropped marks were excluded. The datasets are the grades of the students enrolled in BC and AE 113 and 114 for the school year, 2018–2019 and 2019–2020. Findings: Results showed a very good rating of the student’s performance in all courses both bridging course and accounting education courses where it revealed a positive and linear relationship. Moreover, the model shows that an increase in the performance in the BC is an increase also in their performance in their AE courses. Conclusion: The study proved that the curriculum is serving its purpose in rendering the highest possible opportunity for students to learn basic and even advanced accounting education.Keywords: accounting performance, bridging course, educational data mining, modelling.DOI: http://dx.doi.org/10.23960/jpp.v11.i3.202103